Умова повного вимітання та її узагальнення у диференціальних іграх - Ostapenko, V. V.; Yakunina, I. L.; Tereshchenko, I. N.; Amirgalieva, S. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Differential games with fixed finishing time are considered. Sets of the initial positions favourable for pursuer and escaper are described. Under the conditions of full sweep with separated controls, alternative theorems are valid. Games are considered separately from the positions of pursuer and escaper. The strategies of players for various classes of games and for advantages of each player are described.